Um estudo da vulnerabilidade socioclimática no Brasil e no mundo - Darela Filho, João Paulo [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The Socio Climate Vulnerability Index (IVSC, Portuguese acronym) aims to expose spatially and in a comparative basis, human settlement areas that are more susceptible to the potential risks posed by climate change. To access this vulnerability, the IVSC draws on the aggregation of adaptive capacity and sensitivity indicators (Human Development Index and population density) and an indicator of projected climate change (Regional Climate Change Index-IRCM). The IVSC can be applied to any spatial scale, as long as data in reasonable resolution.is available. Knowing the spatial distribution of vulnerability is an important strategic step in development and implementation of measures that seeks to improve human development and the preparedness of society for future environmental changes. In addition, the production and comparison climate change vulnerability indexes is an important exercise to improve gradually the quality of information provided to decision makers and stakeholders in the management of measures involving climate change adaptation

O Índice de Vulnerabilidade Socioclimática (IVSC) tem como objetivo explicitar espacialmente, numa base comparativa, zonas de ocupação humana que se encontrem mais suscetíveis aos possíveis riscos gerados pelas mudanças climáticas. Para acessar essa vulnerabilidade, o IVSC vale-se da agregação de indicadores de capacidade adaptativa e sensibilidade (Índice de Desenvolvimento Humano; densidade populacional) atuais, a indicadores de intensidade das mudanças climáticas futuras (Índice Regional de Mudanças Climáticas- IRCM). O IVSC pode ser aplicado em qualquer escala espacial, contanto que existam dados em resolução adequada. Conhecer a distribuição espacial da vulnerabilidade é um importante passo estratégico para a elaboração e implantação de medidas que visem o progresso no desenvolvimento humano e a adequação da sociedade para um futuro de mudanças ambientais. Além disso, a produção e comparação de índices de vulnerabilidade às mudanças climáticas é um importante exercício na busca por melhorar, progressivamente, a qualidade da informação fornecida a tomadores de decisão e outras partes interessadas no manejo de medidas visando adaptação às alterações do clima
Keywords: Climatologia; Mudanças climáticas; Ecologia humana; Brasil